Aligning OCL with UML - Willink, Edward (Electronic Communications of the EASST, 2011)
OCL is widely used by UML and other languages to constrain meta-models and perform evaluations on models.Unfortunately no OCL 2.x specification has ever been aligned with any UML 2.x specification. This lack of alignment makes some OCL compliance points such as XMI interchange unachievable. This paper describes how introduction of an OCL Pivot Meta-Model and clear exposition of the Values package may provide a solution to the alignment and a variety of other specification issues.